THE CORRELATION STUDY BETWEEN STUDENTS’ LEARNING STYLES AND SPEAKING ABILITY - Ayu Indah Karisma; Intan Hamzah (Indonesian Journal of Educational Development (IJED), 2025)
The study aims to examine whether there is any important association between learning style and students’ Speaking ability. The method used in this study is a quantitative survey by questionnaire. The sample for this study consisted of 42 students studying English Education at Universitas Teknokrat Indonesia. To analyze the information, the analysts utilized SPSS Windows 21. The investigation yields a least score of 70, a greatest score of 90, and an average score of 85. Based on the results of this consideration, it can be concluded that there's a positive relationship between the utilization of learning styles and speaking ability. The educational implications of English teachers' proposals to train English learners to adopt language learning styles and improve their speaking ability between learning style and speaking ability of students.